2022
DOI: 10.1039/d1py01604k
|View full text |Cite
|
Sign up to set email alerts
|

A multi-functional chromone-modified polyethylene obtained by metal-free C–H activation

Abstract: Post-modification of polyolefins via cutting-edge C−H activation has recently emerged as an attractive methodology for the incorporation of precise functionalities, thus expanding their applicability and creating value-added materials. In this...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…In 2019, Zhou and coworkers demonstrated that chromones could serve as the acceptor in a thermal C( sp 3 )−H functionalization of PE in the presence of commercially available, inexpensive DTBP as the oxidant (Scheme 2). [10] Up to 4.05 mol % functionality in P1 was yielded when the reaction was performed with 30 equivalent of chromone and 10 equivalent of DTBP in 100 wt % of melting naphthalene (NAP). The incorporation of chromone moiety onto PE exhibited several intriguing properties including antioxidation and fluorescence properties, allowing the modified samples to be used as polymer‐bound antioxidants and fluorescence markers for plastic sorting.…”
Section: Upcycling Of Polyolefins Into New Polymeric Materialsmentioning
confidence: 99%
“…In 2019, Zhou and coworkers demonstrated that chromones could serve as the acceptor in a thermal C( sp 3 )−H functionalization of PE in the presence of commercially available, inexpensive DTBP as the oxidant (Scheme 2). [10] Up to 4.05 mol % functionality in P1 was yielded when the reaction was performed with 30 equivalent of chromone and 10 equivalent of DTBP in 100 wt % of melting naphthalene (NAP). The incorporation of chromone moiety onto PE exhibited several intriguing properties including antioxidation and fluorescence properties, allowing the modified samples to be used as polymer‐bound antioxidants and fluorescence markers for plastic sorting.…”
Section: Upcycling Of Polyolefins Into New Polymeric Materialsmentioning
confidence: 99%